The Relationship Between Brainstem Temporal Processing and Performance on Tests of Central Auditory Function in Children With Reading Disorders. - Billiet, Cassandra R.; Bellis, Teri James (Journal of Speech, Language & Hearing Research, 2011)
Purpose: Studies using speech stimuli to elicit electrophysiologic responses have found approximately 30% of children with language-based learning problems demonstrate abnormal brainstem timing. Research is needed regarding how these responses relate to performance on behavioral tests of central auditory function. The purpose of the study was to investigate performance of children with dyslexia with and without abnormal brainstem timing and children with no history of learning or related disorders on behavioral tests of central auditory function. Method: Performance of 30 school-age children on behavioral central auditory tests in common clinical use was examined: Group 1 (n = 10): dyslexia, abnormal brainstem timing; Group 2 (n = 10): dyslexia, normal brainstem timing; Group 3 (n = 10): typical controls. Results: Results indicated that all participants in Group 2 met diagnostic criteria for (central) auditory processing disorder [(C)APD], whereas only 4 participants in Group 1 met criteria. The Biological Marker of Auditory Processing (BioMARK) identified 6 children in Group 1 who did not meet diagnostic criteria for (C)APD but displayed abnormal brainstem timing. Conclusions: Results underscore the importance of central auditory assessment for children with dyslexia. Furthermore, the BioMARK may be useful in identifying children with central auditory dysfunction who would not have been identified using behavioral methods of (C)APD assessment. Reprinted by permission of the publisher.